Facile synthesis of 1D-architecture of silver-vanadates in carbon nest for enhanced visible light driven photo-oxidation process. Issue 2 (April 2018) - Das, Biraj; Sharma, Mukesh; Deka, Biplab K.; Hazarika, Ankita; Park, Young-Bin; Hazarika, Anil; Bhargava, Suresh K.; Bania, Kusum K.
Graphical abstract: Complete mineralization of MB dye with Ag/AgCl/V2 O5 -MWCNT nanocomposite under sun light. Highlights: Ag/AgCl/V2 O5 with 1D architecture is synthesized in Multiwalled Carbon Nanotube. Ag/AgCl/V2 O5 -MWCNT appeared as suitable photocatalyst absorbing visible light of solar spectrum. Creation of defects in MWCNT enhanced the photocatalytic ability of the nanomaterial. The hybrid nanocomposite decompose methylene blue dye with high efficiency within 25 min under sunlight. The photocatalyst was recyclable for three consecutive cycles. Abstract: Ag/AgCl/V2 O5 nanocatalysts with one dimensional (1D) architecture was synthesized in carboxylic acid functionalized multi-walled carbon nanotubes for methylene blue dye degradation. The growth of uniformly distributed nanoparticles along the carbon-nanotubes was revealed from high resolution transmission electron microscopy and atomic force microscopy analyses. Raman spectroscopy and transmission electron microscopy analyses also confirmed for the creation of defects in the multi-walled carbon nanotube. The hybrid nanocomposite appeared as a suitable photocatalyst for degradation of methylene blue dye absorbing the light in the visible range of solar spectrum. The presence of interactions within the nanoparticles and with the nanotubes was believed to enhance the photo-oxidation process. The creation of defects in the carbon nanotube on modification with Ag/AgCl/V2 O5 improved the photocatalytic activity by enhancing the photoelectron transfer process. About ∼90% of the total organic carbon of the dye molecule was found to decompose into CO2, H2 O and inorganic ions within 25 min under sunlight.